Design And Fabrication Of Multipurpose Smart Phantom For Positron Emission Tomography/Computed Tomography Imaging - Zainon, Rafidah (2008)

(untitled)
Phantom studies are an important part in medical imaging as it can evaluate the performance and quality assurance (QA) test of dual-modality PET/CT. The purpose of this study is to, design, fabricate and develop a multipurpose smart phantom which includes the internal structures, water, human tissue equivalent materials and radioactive source for dual-modality Positron Emission Tomography/Computed Tomography (PET/CT) imaging. In this study, experimental determination of Hounsfield units (HU), mass attenuation coefficient, elemental composition analysis and structure analysis were performed on phantom materials using PET/CT scanner, Multichannel Analyser (MCA), CI-INS analyser and Scanning Electron MicroscopelEnergy Dispersive X-Ray (SEMlEDX) respectively. Kajian fantom adalah bahagian yang penting dalam pengimejan perubatan kerana ia dapat menilai pedaksanaan dan ujian jaminan kualiti (QA) dwi-modaliti Tomografi Pancaran Positronffomografi Berkomputer {PETtCT). Tujuan kajian ini adalah untuk merekabentuk, memfabrikasi dan membangunkan fantom pintar pelbagai tujuan yang termasuk struktur dalaman, air, bahan-bahan setara dengan tisu manusia dan sumber radioaktif untuk pengimejan dwi-modaliti PETtCT. Dalam kajian ini, penentuan secara eksperimen Unit Hounsfield (HU), pekali atenuasi jisim, analisis komposisi elemen dan analisis struktur telah dilakukan terhadap bahan-bahan fantom menggunakan PETtCT skan, Penganalisis Berbilang Saluran (MCA), Penganalis CHNS dan Pengimbas -Mikroskop ElektronIKeselerakan Tenaga X-ray (SEMlEDX) masing-masing.